Konsekuensi Place Attachment Konsumen Restoran Bertema Sunda - Aprilia, Risma; Laddyana Citra, Febby; Vandayuli Riorini, Sri (Fakultas Ekonomi Universitas Gresik, 2023)
This research was conducted with the aim of analyzing the effect of Place Attachment on Brand Loyalty of Sundanese themed restaurant customers. This study is an explanatory research with a total sample of 270 respondents who were taken using a non-probability sampling method with the technique used was purposive sampling. The data were analyzed using the AMOS Structural Equation Model. The results of this study prove that Layout has an influence on Brand Passion, Brand Love and Brand Loyalty. Research also proves that Brand Identification has a significant effect on Brand Love